Alterations in White Matter Integrity in Young Adults with Smartphone Dependence - Hu, Yuanming; Long, Xiaojing; Lyu, Hanqing; Zhou, Yangyang; Chen, Jianxiang (Frontiers in Human Neuroscience, 2017)
Smartphone dependence (SPD) is increasingly recognized as a mental health disorder, however, the underlying neural substrates of SPD is still not clear. High resolution magnetic resonance imaging provides a useful tool to help understand and manage the disorder. In this study, a tract-based spatial statistics (TBSS) analysis on diffusion tensor imaging (DTI) was used to investigate white matter integrity in young adults with SPD. A total of forty-nine subjects were recruited and categorized into SPD and control group based on their clinical behavioral tests. Whole brain voxel-wise analysis of fractional anisotropy (FA) and mean diffusivity (MD) was performed by TBSS to localize abnormal white matter regions between groups. The correlation between the quantitative variables of brain structures and the behavior measures were performed. Our result demonstrated that SPD had significantly lower white matter integrity than controls in superior longitudinal fasciculus, superior corona radiata, internal capsule, external capsule, sagittal stratum, fornix/stria terminalis, and midbrain structures. Correlation analysis showed that the observed abnormalities in internal capsule and stria terminalis were correlated with the severity of dependence and behavioral assessments. Our finding provided a primary understanding of white matter characteristics in SPD and indicated that the deficits might link to behavioral impairments.